2015
DOI: 10.1155/2015/324265
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Extract ofPerilla frutescensSuppresses Allergen-Specific Th2 Responses and Alleviates Airway Inflammation and Hyperreactivity in Ovalbumin-Sensitized Murine Model of Asthma

Abstract: This study was to investigate the effects of different fractions of Perilla frutescens (Pf) leaves extracted by water or ethanol on asthma. BALB/c mice sensitized intraperitoneally and challenged with ovalbumin (OVA) were divided into six groups. Each group of mice was tube-feeding with 0 (control), 80 μg (PfWL), or 320 μg (PfWH) water extracts or 80 μg (PfEL) or 320 μg (PfEH) ethanol extracts of perilla leaves daily for 3 weeks. A negative control group (PBS) was neither sensitized nor treated with Pf. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Many reports have highlighted the efficacy of immunomodulatory and anti-inflammatory agents to treat patients with asthma, thus it is likely to hypothesize that honey, which is cheap and readily available natural product may also be a potential therapeutic agent for asthma. 10 , 11 , 12 , 13 To our knowledge, no comprehensive studies thus far have addressed whether ingestion of honey is effective to treat allergic asthma. Therefore, this study is aimed to investigate the efficacy of Malaysian Gelam honey on the mediator and lung histopathology in a murine model of allergic asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have highlighted the efficacy of immunomodulatory and anti-inflammatory agents to treat patients with asthma, thus it is likely to hypothesize that honey, which is cheap and readily available natural product may also be a potential therapeutic agent for asthma. 10 , 11 , 12 , 13 To our knowledge, no comprehensive studies thus far have addressed whether ingestion of honey is effective to treat allergic asthma. Therefore, this study is aimed to investigate the efficacy of Malaysian Gelam honey on the mediator and lung histopathology in a murine model of allergic asthma.…”
Section: Introductionmentioning
confidence: 99%
“…The main effective components from different parts of PF mainly contained phenolic compounds, flavonoids and triterpenes . Researches have been reported that water extract from PF could down‐regulate both matrix metalloproteinase‐9 and interleukin‐31 expression, which relieved the inflammation in C57BL/6 mice . While the ethanol extract of PF was proved to be effective in suppressing the allergen‐specific Th2 responses .…”
Section: Introductionmentioning
confidence: 99%
“…Researches have been reported that water extract from PF could down‐regulate both matrix metalloproteinase‐9 and interleukin‐31 expression, which relieved the inflammation in C57BL/6 mice . While the ethanol extract of PF was proved to be effective in suppressing the allergen‐specific Th2 responses . It was also reported that ROS from PF could alleviate the allergic inflammatory reactions by reducing the cytokine products in mice serum, like IgE and histamine, and inhibiting the cytokine expression, like IL‐1β, IL‐6 and TNF‐α .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated the effect of the petroleum ether, chloroform, ethyl acetate and n-butanol layers on Th1/Th2 balance, the mRNA levels of several CysLTs and pathophysiological changes in lung tissues in an allergic asthma mouse model. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%